Development of a Local Wisdom Mapping Application to Support P5 Learning at SMA Negeri 5 Bandung - Suprapto, Falahah; Fajar, Abdullah; Munandar, Fajar (LPPM STIKI MALANG, 2024)
Local wisdom is a valuable national cultural asset that needs to be preserved. We can initiate an effort to preserve local wisdom by disseminating it to the broader community through comprehensive and precise information. However, Indonesia has not yet effectively managed local wisdom information, forcing individuals to scour the internet for various sources. On the other hand, the education sector also places significant emphasis on local wisdom, incorporating it as a key theme in the implementation of the P5 (Projek Penguatan Profil Pelajar Pancasila) program in schools. P5 is a project-based learning approach that has become mandatory from the latest education curriculum (Kurikulum Merdeka). Through teamwork, P5 assigns students to study a specific subject or social or cultural phenomenon. This assignment culminates in the presentation of a report or a specific product. P5 typically collects reports and information in hard copy form, only archiving them at the school, making it challenging for both students and the wider community to access them. Indeed, easy access to the collected information would greatly enhance its usefulness. Based on the aforementioned conditions, we proposed a solution that involves building and implementing a local wisdom mapping application for the storage of digital data. The P5 programs at Senior High School 5 (SMA Negeri 5) Bandung, which selected local wisdom as a specific theme for P5, serve as the data source for this application. It is expected that the presence of this application can support the P5 learning process by facilitating digital storage of research results and disseminating the results to a wider community. We conducted this study using the canonical action research method. Two classes of 10th-grade students participated in the implementation and socialization phases of the pilot project. They can input a location and complementary information such as related photos and videos and complete student research reports. It helps the student keep their work published and reachable by the broader community. The evaluation results demonstrate the application's ease of use and benefits for students and the school.